2007
DOI: 10.1179/174329407x174425
|View full text |Cite
|
Sign up to set email alerts
|

Heat treated anodised titanium surfaces showing enhanced photocatalytic inhibition of microbial fouling

Abstract: Titanium, an otherwise perfect condenser tube material in sea water applications, is challenged by the problem of severe biofouling. Anatase, one of the two commercially important crystalline forms of titanium dioxide, possesses excellent photocatalytic activity (PCA). It has been shown in the earlier studies by the authors that anodisation of titanium produces anatase type of TiO 2 capable of photocatalytic inhibition of microbial adhesion under near UV light illumination. The present study investigates the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…This is why the extent of the damage incurred to the bacterial cells is not correctly portrayed nor reflected by the plate count technique. Such an observation has been reported by Gopal et al 19 when working with TiO 2 based inhibiton of bacterial cells. They have reported a two-order difference between the total viable counts determined by the plate count method and direct acridine orange counts taken by viewing under an epifluorescence microscope.…”
Section: Acknowledgmentsupporting
confidence: 76%
“…This is why the extent of the damage incurred to the bacterial cells is not correctly portrayed nor reflected by the plate count technique. Such an observation has been reported by Gopal et al 19 when working with TiO 2 based inhibiton of bacterial cells. They have reported a two-order difference between the total viable counts determined by the plate count method and direct acridine orange counts taken by viewing under an epifluorescence microscope.…”
Section: Acknowledgmentsupporting
confidence: 76%
“…In order to increase the thickness of the film, it is locally necessary to provide the proceeding of the process by breaking barrier film which has insulating properties. Previous investigations have shown that the properties of the titanium oxide films produced with anodization are affected by electrochemical parameters such as ion current density, solution, temperature and applied voltage [10][11][12]. Kuromota et al [13] pointed out that the morphology and thickness of anodic oxide films strongly depended on the applied voltage.…”
Section: Introductionmentioning
confidence: 98%
“…27 Gopal et al report the successful use of the anatase type of TiO 2 for the inactivation of bacteria using anatase TiO 2 thin films. [28][29][30][31] The mechanism of photocatalytic inhibition is that upon excitation by light whose wavelength is less than 385 nm, the photon energy generates an electron-hole pair on the TiO 2 surface. The hole in the valance band can react with H 2 O or hydroxide ions adsorbed on the surface to produce hydroxyl radicals (OH À ), and the electron in the conduction band can reduce O 2 to produce superoxide ions radicals (O À ).…”
Section: Discussionmentioning
confidence: 99%
“…report that two mechanisms seem to be operating, one through the direct oxidation by the positive holes and the other indirect oxidation by the formation of free radicals. 30,36 Direct oxidation by the positive holes results in oxidative stress within the cells which induces the formation of free radicals, which can bring about cell death. 37 Indirect oxidation involves the production of free radicals by the electron holes on the oxide surface.…”
Section: Discussionmentioning
confidence: 99%